Trichobezoar masquerading as massive splenomegaly: Rapunzel’s syndrome revisited - Zhi, Alex Yang Koh; Larry Ellee Nyanti; Lim, Sheri; Tien, Loong Luk; Sing, Andy Ong Tang; Tze, Shin Leong; Lee, Ping Chew (Elsevier, 2022)
Trichobezoars are usually formed due to ingestion of hair or hair-like fibres and present with a wide spectrum of clinical manifestations. We report a case of Rapunzel’s syndrome associated with trichotillomania in a 16-year-old girl who presented to our Haematology unit with complaints of fatigue, abdominal distention, and early satiety. Initial evaluation demonstrated anaemia, thrombocytosis, and a left hypochondrial mass suggestive of splenomegaly. However, ultrasound of the abdomen showed no hepatosplenomegaly and blood investigations were not suggestive of haematological malignancy. Not long after, the patient presented to the emergency department with suspected acute abdomen. Computed tomography of the abdomen revealed intraluminal gastric and jejunal masses causing small bowel obstruction. Emergency laparotomy confirmed gastric and jejunal trichobezoars, and subsequent psychiatric evaluation confirmed trichotillomania. Clinicians should consider trichobezoar in the differential diagnosis of abdominal pain and a non-tender ‘spleen-like’ abdominal mass.